Neutralizing antibodies and fatigue as predictors of low response to interferon-beta treatment in patients with multiple sclerosis - Manceau, Philippe (BMC Neurol, 2014)
BACKGROUND: The clinical impact of neutralizing antibodies against interferon-beta (NAb) is controversial. Their presence can lead to a decrease in interferon-beta (IFNβ) efficacy. Fatigue reported in patients with multiple sclerosis (MS) may be associated with an unfavorable clinical course. We conducted a prospective multicentre study to assess the association between response to IFNβ, NAb and fatigue. METHODS: Patients with relapsing-remitting MS on IFNβ treatment were included. During the second year of treatment, the patients were analyzed for NAb status and non-response criteria to IFNβ (number of relapses ≥1 during the follow-up period, increase in the Expanded Disability Status Scale ≥0.5). The score on the Modified Fatigue Impact Scale (MFIS pathological if score ≥35) was noted for each patient. RESULTS: Of the 176 patients included: 22.3% were NAb positive, 54.5% presented non-response criteria to IFNβ, and 57.4% had a pathological MFIS score. Fatigue was increased in NAb + patients (p = 0.0014) and they were more likely to present non-response criteria to IFNβ (p = 0.041) than NAb- patients. Multivariate logistic regression analysis showed that the presence of NAb was related to fatigue (p = 0.0032) and denoted disease activity in these patients (p = 0.026). CONCLUSIONS: This study demonstrates the impact of NAb on the non-clinical response to IFNβ. Fatigue assessment is an indicator of IFNβ responsiveness and a predictive biomarker of deterioration on patient’s neurological status.